2014
DOI: 10.1111/jbi.12409
|View full text |Cite
|
Sign up to set email alerts
|

Of peaks and valleys: testing the roles of orogeny and habitat heterogeneity in driving allopatry in mid‐elevation frogs (Aromobatidae: Rheobates) of the northern Andes

Abstract: Aim The frog genus Rheobates (Anura: Aromobatidae) is endemic to mid-elevations in the Colombian Andes. Our aim was to evaluate the role of the northern Andean high peaks and the low Magdalena Valley in creating barriers to dispersal and promoting vicariance within Rheobates.Location Three disjunct mid-elevation flanks of the northern Colombian Andes: the eastern and western flanks of the Eastern Cordillera, separated by high mountain peaks, and the eastern flank of the Central Cordillera, separated from the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 62 publications
5
44
1
2
Order By: Relevance
“…Cryptic diversity is an essential component of diagnosing biodiversity, and it is difficult to detect, especially under ongoing global climate change and habitat loss (Balint et al., ; Bickford et al., ). Empirical studies have identified evolutionary patterns of cryptic diversity similar to our study in other biodiversity hotspots (Bell et al., ; Carnaval, Hickerson, Haddad, Rodrigues, & Moritz, ; Demos, Peterhans, Agwanda, & Hickerson, ; Hedin, Carlson, & Coyle, ; Muñoz‐Ortiz, Velásquez‐Álvarez, Guarnizo, & Crawford, ; Wachter et al., ). However, previous studies did not consider the role of niche conservatism in impacting cryptic speciation.…”
Section: Discussionsupporting
confidence: 84%
“…Cryptic diversity is an essential component of diagnosing biodiversity, and it is difficult to detect, especially under ongoing global climate change and habitat loss (Balint et al., ; Bickford et al., ). Empirical studies have identified evolutionary patterns of cryptic diversity similar to our study in other biodiversity hotspots (Bell et al., ; Carnaval, Hickerson, Haddad, Rodrigues, & Moritz, ; Demos, Peterhans, Agwanda, & Hickerson, ; Hedin, Carlson, & Coyle, ; Muñoz‐Ortiz, Velásquez‐Álvarez, Guarnizo, & Crawford, ; Wachter et al., ). However, previous studies did not consider the role of niche conservatism in impacting cryptic speciation.…”
Section: Discussionsupporting
confidence: 84%
“…The three cordilleras are separated by dry and deep basins; the Cauca basin separates the West and Central cordilleras, and the Magdalena basin separates the Central and East cordilleras. Montane forests are also interrupted at high elevations (> 3000 m), where the slopes of each cordillera are separated by ridgelines often above 4000 m. If the complex topography of the Colombian Andes defines metapopulations in resident species of birds and other organisms (Guti errez-Pinto et al, 2012;Muñoz-Ortiz et al, 2014), the same may apply to migratory species. Indeed, a number of studies have shown the differential use of Caribbean islands and Central America by populations of migratory birds (Rubenstein et al, 2002;Norris et al, 2006), and so, it follows that the Andes could act as 'islands in the sky' for migratory montane specialists.…”
Section: Introductionmentioning
confidence: 99%
“…The asynchrony in timing of divergence makes this explanation less likely, however. Alternatively, polyphyly could be created by multiple crossings of the EC following an initial vicariant separation, as found in, for example, the bird Mionectes (Miller et al, 2008) and the frog, Rheobates (Muñoz-Ortiz et al, 2015), suggesting that the EC-MA is an ineffective barrier for half of tetrapod lineages studied here. Such a model of recent dispersal across a fully formed Andes could explain the heterogeneity in divergence times among lineages, the overall young ages relative to the old age of the EC-MA as synthesized here, and the young divergence times among homeotherms relative to poikilotherms (Fig.…”
Section: Discussionmentioning
confidence: 88%